Big data analytics for smart and connected cities - Dey, Nilanjan 1984-; Tamane, Sharvari 1973- (IGI Global, 2019)
"This book explores the concepts of big data, IoT and Smart Cities along with the recent research development. It also includes various real time and offline applications and case studies in the field of engineering, computer science, IoT, Smart Cities with modern tools and technologies used"...